REALITAS PROFETIK DALAM NOVEL KETIKA CINTA BERTASBIH KARYA HABIBURRAHMAN EL-SHIRAZY - Anwar Efendi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the prophetic reality in Ketika Cinta Bertasbih, a novel by Habiburrahaman El-Shirazy. It employed a structural-dynamic (semiotic) approach and the data were analyzed using content analysis. The results are as follows. First, the prophetic reality in the humanization aspect appears in the presence of a human being figure trapped in the vortex of life modernity. Second, the prophetic reality in the liberation aspect is related to the relation of men and women in individual and social perspectives. Third, the prophetic reality in the transcendence aspect is related to the awareness of God and longing for eternal life.